2019
DOI: 10.1186/s13036-019-0215-y
|View full text |Cite
|
Sign up to set email alerts
|

Unique N-glycosylation of a recombinant exo-inulinase from Kluyveromyces cicerisporus and its effect on enzymatic activity and thermostability

Abstract: BackgroundInulinase can hydrolyze polyfructan into high-fructose syrups and fructoligosaccharides, which are widely used in food, the medical industry and the biorefinery of Jerusalem artichoke. In the present study, a recombinant exo-inulinase (rKcINU1), derived from Kluyveromyces cicerisporus CBS4857, was proven as an N-linked glycoprotein, and the removal of N-linked glycan chains led to reduced activity.ResultsFive N-glycosylation sites with variable high mannose-type oligosaccharides (Man3–9GlcNAc2) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…The recombinant inulinase (INU1) from K. marxianus NCYC2887 overexpressed by Saccharomyces cerevisiae showed an apparent MW of 98 kDa, bigger than its theoretical 59 kDa 35 . The increase of apparent MW may probably be attributed to the post‐translational N‐glycosylation, as demonstrated in the exo‐inulinase from K. cicerisporus expressed in Pichia pastoris X‐33 with theoretical MW of 60.54 kDa and apparent MW of 79.5 kDa 36 …”
Section: Resultsmentioning
confidence: 95%
“…The recombinant inulinase (INU1) from K. marxianus NCYC2887 overexpressed by Saccharomyces cerevisiae showed an apparent MW of 98 kDa, bigger than its theoretical 59 kDa 35 . The increase of apparent MW may probably be attributed to the post‐translational N‐glycosylation, as demonstrated in the exo‐inulinase from K. cicerisporus expressed in Pichia pastoris X‐33 with theoretical MW of 60.54 kDa and apparent MW of 79.5 kDa 36 …”
Section: Resultsmentioning
confidence: 95%
“…To enhance thermostability, K. marxianus exo-inulinase was fused to the inulin-binding module from the N-terminal region of Bacillus macerans cycloinulinooligosaccharide fructanotransferase [ 8 ]. Ma et al reported that the thermostability of Kluyveromyces cicerisporus exo-inulinase was changed when five N-glycosylation sites (Asn362, Asn370, Asn399, Asn467, and Asn526) at the C-terminus were substituted with glutamines [ 21 ]. This study firstly showed that thermostability of exo-inulinases were affected by N-terminal tail.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional model of KcINU1 was obtained as described previously ( Ma et al, 2019 ). The model was automatically built through the Swiss-Model server 3 using the crystal structure of exo-inulinase INU1 (PDB code 6J0T) as the template which sharing 98.2% sequence identity with the KcINU1.…”
Section: Methodsmentioning
confidence: 99%
“…Site-directed mutations were performed using RF cloning method the same as previously described ( Ma et al, 2019 ). The pPICZαA-rKcINU1 recombinant plasmid was used as the template, and primers ( Supplementary Table 1 ) used in RF-cloning were designed by online service tool 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation